Efeito do extrato clorofórmico do cerne de Platymiscium floribundum vog, de um composto isolado (6,7-mimetoxicumarina) e de seu derivado semissintético (6,7-dimetoxi-3-nitrocumarina) em um ensaio pré-clínico de periodontite. - Freire, Jordânia Marques de Oliveira (2018)
Periodontitis is an immuno-inflammatory disease, which can lead to tooth loss. The treatment includes non-surgical or surgical therapy, with or without nonsteroidal anti-inflammatory drugs and/or antibiotics. The main concern about the adjunct therapy is the occurrence of side effects (bacterial resistance, gastrointestinal, cardiovascular, and renal effects). Thus, the search for drugs with a better risk/benefit ratio still continues. Natural products from plants are considered alternatives to synthetic chemicals. Platymiscium floribundum Vog. is a Brazilian tree which has been used in folk medicine as an anti-inflammatory agent. This study aimed to investigate the efficacy of P. floribundum, of the isolated 6,7- dimethoxycoumarin compound and the semisynthetic compound 6,7-dimethoxy-3- nitrocoumarin in a model of periodontitis. Periodontitis was induced by placing a nylon thread in the molars of female Wistar rats (200-220g). Rats were tretated with P. floribundum (0.1, 1 or 10 mg/kg) or vehicle 1h before periodontits-challenge and once daily during 11 days. On the 11th day, rats were euthanized, under anesthesia, and it was harvested the maxillae - for morphometric (ImageJ® software), hystopathological (H&E), and Scanning Electron Microscopic analysis (SEM) analysis - and gingival samples for (1) Myeloperoxidase (MPO) activity, (2) nitrite/nitrate levels, (3) superoxide dismutase-SOD/catalase-CAT levels, (4) TNF-α, IL1-β, IL-8/CINC-1, IL-10, and PGE2 levels (ELISA), and (5) qRT-PCR for TNF-α, IL1-β, COX-2, iNOS, RANK and RANKL. Blood samples were collected at 11th day for AST, ALT, creatinine, total alkaline phosphatase (TALP), and bone alkaline phosphatase (BALP) dosage. P. floribundum (10mg/kg) decreased alveolar bone loss, MPO activity nitrite/nitrate levels, oxidative stress, TNF-α, IL1-β, IL-8/CINC-1, and PGE2 gingival levels, and transcription of TNF-α, IL1-β, COX-2, iNOS, RANK, and RANKL genes, while elevated both BALP serum levels and IL-10 gingival levels. The animals did not show signs of toxicity throughout the experimental course. Compounds 6,7-dimethoxycoumarin and 6,7-dimethoxy- 3-nitrocoumarin (1 mg / kg) also decreased levels of bone resorption. These findings show that P. floribundum has anti-inflammatory and anti-resorptive and that its isolated and semisynthetic compounds represent an interesting biotechnological tool.